2014
DOI: 10.2323/jgam.60.227
|View full text |Cite
|
Sign up to set email alerts
|

Pyrosequencing-based analysis of the bacterial community during fermentation of Alaska pollock sikhae: traditional Korean seafood

Abstract: We analyzed the bacterial community of Alaska pollock sikhae, a traditional Korean food made by natural fermentation with Alaska pollock, utilizing pyrosequencing. We fermented the Alaska pollock sikhae at two different temperatures (10 C and 20 C). Before fermentations, the bacterial community was varied. After fermentations, however, Lactobacillus sakei became dominant. The Alaska pollock sikhae sample before fermentations contained only 2% L. sakei, but the sample on day 6 of fermentation at 10 C comprised … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 46 publications
(70 reference statements)
0
9
0
Order By: Relevance
“…This species is often associated with various meat fermentations [36] and one of relatively few LAB able to grow in the salt concentrations and the ripening temperatures applied during rakfisk fermentations [37,38]. L. sakei was also found to be the dominant LAB in sikhae and gajami-sikhae, mild-salted fermented fish products from Korea [15]. The Chinese product Suan Yu , with some similarities to rakfisk fermentation [10], but fermented at higher temperature, was shown by microbiota analysis to be quickly dominated by Firmicutes and lactobacilli with higher temperature preferences, such as L. plantarum [39].…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…This species is often associated with various meat fermentations [36] and one of relatively few LAB able to grow in the salt concentrations and the ripening temperatures applied during rakfisk fermentations [37,38]. L. sakei was also found to be the dominant LAB in sikhae and gajami-sikhae, mild-salted fermented fish products from Korea [15]. The Chinese product Suan Yu , with some similarities to rakfisk fermentation [10], but fermented at higher temperature, was shown by microbiota analysis to be quickly dominated by Firmicutes and lactobacilli with higher temperature preferences, such as L. plantarum [39].…”
Section: Discussionmentioning
confidence: 99%
“…This taxon has been found dominant in shellfish [18] and in cured skate [41]. However, several studies found Gammaproteobacteria as a non-dominant part of the bacteria in fermented food [42,43,44] or found that the domination of this taxon has been replaced by Firmicutes towards the end of the fermentation [15,45,46]. In our study, Gammaproteobacteria was dominating in the brine when rakfisk was produced with a high salinity combined with a low ripening temperature.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations